2020
DOI: 10.3389/fcvm.2020.614031
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Catheter Ablation for Patients With Atrial Fibrillation and Heart Failure

Abstract: The coexistence of atrial fibrillation and heart failure significantly increases the risk of all-cause mortality and heart failure hospitalizations. Sex-related differences in all patients undergoing atrial fibrillation catheter ablation include the referral of fewer women for catheter ablation (15–25%), older age of women at ablation, and higher risk of post-ablation recurrence of atrial fibrillation. We searched the existing literature for sex-related differences in patients undergoing atrial fibrillation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This comprehensive review of the literature highlights disparities based on gender in the utilization of DBS for PD, which aligns with prior research examining disparities in access to invasive treatments for cardiac and gastrointestinal conditions (Hvelplund et al, 2010;Chibber and Baranchuk, 2020). Several studies have identified a notable gender disparity in the utilization of DBS for PD, with a significantly higher proportion of men undergoing the procedure than women and these studies have been conducted in various countries (Hariz et al, 2003(Hariz et al, , 2013Mathkour et al, 2017;Deshpande et al, 2022).…”
Section: Gender Disparitiessupporting
confidence: 68%
“…This comprehensive review of the literature highlights disparities based on gender in the utilization of DBS for PD, which aligns with prior research examining disparities in access to invasive treatments for cardiac and gastrointestinal conditions (Hvelplund et al, 2010;Chibber and Baranchuk, 2020). Several studies have identified a notable gender disparity in the utilization of DBS for PD, with a significantly higher proportion of men undergoing the procedure than women and these studies have been conducted in various countries (Hariz et al, 2003(Hariz et al, , 2013Mathkour et al, 2017;Deshpande et al, 2022).…”
Section: Gender Disparitiessupporting
confidence: 68%
“…Multiple risk factors, including unmodifiable risk factors (e.g., gender, age, and genetics) and modifiable risk factors (e.g., hypertension, DM, and obesity), played a significant role in contributing to the initiation and progression of AF. A growing number of clinical studies have suggested that female patients have a higher risk of AF recurrence than male patients after ablation, owing to more advanced atrial remodeling [ 44 , 45 ]. The recurrent AF subanalysis in the CABANA trial (NCT00911508) proved that the efficacy of ablation in the female subgroup was significantly inferior to that in the male subgroup when compared with the efficacy of drug therapy (HR: 0.64 vs. 0.46, p for interaction = 0.035) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…e occurrence of atrial fibrillation will increase the chance of thrombosis in patients, and heart failure can easily induce atrial fibrillation, both of which threaten people's health [2,3]. erefore, improving the accuracy in diagnosing atrial fibrillation combined with heart failure is the first priority.…”
Section: Introductionmentioning
confidence: 99%